Jorge Lobo's disease - Kalline Andrade de Carvalho; Marcos César Floriano; Milvia Maria Simões e Silva Enokihara; Marta Regina Machado Mascarenhas (Sociedade Brasileira de Dermatologia, 2015)
AbstractJorge Lobo's Disease is a rare, chronic granulomatous cutaneous mycosis, which is typical of tropical and subtropical regions. It is caused by the traumatic implantation of the fungus Lacazia loboi into the skin and subcutaneous tissue. The disease was first described in 1931 by Jorge Lobo, in Recife (PE), Brazil. It is common in Central and South America, and predominates in the Amazon region. We report a case of Jorge Lobo's Disease, which had been initially referred as being paracoccidioidomycosis. We emphasize clinical and diagnostic features of the disease.